A strategic management based on multicriteria decision analysis: an application for the Alpine regions. (2018) - Oppio, Alessandra; Bottero, Marta
Starting from the case of the Alpine huts located in the Sondrio Province of the Lombardy Region (Italy), the paper proposes an integrated evaluation framework for addressing the need of the Italian Alpine Club to efficiently allocate economic resources in the context of the huts' management. The evaluation has been based on the combination of spatial multicriteria analysis and PROMETHEE method with the aim of defining the most suitable mountain huts to be renovated and valorised. The spatial multicriteria analysis model has allowed to evaluate the huts' system at a territorial macro-scale, putting in evidence the areas with the highest potentialities and those suffering from major risks, while the PROMETHEE application has been targeted to the examination of the huts at a micro-scale, selecting the huts in need of requalification with reference to a set of environmental and functional criteria. The results of the two aforementioned approaches have been merged with the aim of providing an aggregated evaluation of the overall system.